DESIGNING LISTENING MATERIALS BASED ON CONTEXTUAL TEACHING AND LEARNING APPROACH - Sinaga, Dorma Manda Aprianti; Apriliaswati, Rahayu; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
This research was aimed at designing listening materials based on Contextual Teaching and Learning approach for second semester of eleventh grade students of SMA Negeri 1 Ketapang. Before designing the listening materials, the writer did a preliminary study. The result showed that there were not any units which had the seven components of CTL in the units for listening to monologue texts. Therefore, the writer designed listening comprehension materials which fulfilled the seven components of CTL. The listening materials designed had fulfilled the components of CTL, principles of material design, aspects of material design and principles of listening material development. Key words: Contextual Teaching and Learning, Design, Listening